Success and Ideological Use of Historical Novels (Minerva, 2017)
This paper discusses the main reasons for the success of historical novels based on Ancient Rome, and also comments on the main ideological controversies found in these novels. The setting of Rome has been used to defend or attack religious, political and social principles. This is always done from the author’s point of view, who may be an apologist for the Christian faith or critical with it, a defender or an attacker of Marxism, an enthusiastic nationalist or a citizen of the world, uninterested in women issues or a campaigner for the social role of women. It is the novelist’s ideological interests that prevail and this is why the same historical character can be presented from very different angles, as will be shown in relation to Spartacus, Caesar, Julianus, Hannibal or Catilina.
Keywords: historical novel; Rome; success; ideological use